2015
DOI: 10.1080/09537287.2015.1094583
|View full text |Cite
|
Sign up to set email alerts
|

Revitalising energy capital project development and execution strategies: lessons from the energy sector

Abstract: This study sought to examine project delivery challenges currently being faced by energy clients and to determine how they could achieve value creation through better alignment of project delivery processes. There are important lessons to be learned from the energy sector on how to deal with the unique operational and project challenges. Four exploratory focus groups were held with twenty senior project management practitioners, to better understand the greatest needs and project management processes in the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Some used sensitivity analysis and some used external estimating teams, but the UK was the only country mandating reference class forecasting. As with ex-post learning discussed above, a pre-requisite for reference class forecasting is an organisation that collects and maintains the appropriate benchmark data for generating the appropriate forecasts, and this is recognised outside government projects (Fouché & Rolstadås 2010;Ochieng et. al 2016).…”
Section: Optimism Bias and Gamingmentioning
confidence: 99%
“…Some used sensitivity analysis and some used external estimating teams, but the UK was the only country mandating reference class forecasting. As with ex-post learning discussed above, a pre-requisite for reference class forecasting is an organisation that collects and maintains the appropriate benchmark data for generating the appropriate forecasts, and this is recognised outside government projects (Fouché & Rolstadås 2010;Ochieng et. al 2016).…”
Section: Optimism Bias and Gamingmentioning
confidence: 99%
“…Culture related knowledge management has become more and more popular (Ochieng 2009;Ochieng et al 2013;Zuofa and Ochieng 2015;Ovbagbedia and Ochieng, 2015). Economic conditions remain tough due to cut throat competition, globalisation, strategic operations against competition both local and global level (Ochieng et al 2016). Web Portal has become the most essential tool in the energy sector.…”
Section: Perspectives Of Knowledge Management In the Oil And Gas Sectormentioning
confidence: 99%
“…Recently, Abel et al (2015) showed that most of the data relevant for geological interpretation of oil reservoirs entails visual data that have no formal denomination and are learnt through an implicit process during training and field experience. The process of standardising and implementing a knowledge management based system can be particularly difficult for oil and gas companies, which has often viewed key business-exploration, upstream and downstream production, refining as distinctly different (Ochieng et al 2016). Creating a standardised knowledge management model, which entails people and technology approaches, can be challenging (Secchi and Camuffo, 2016;Siemieniuch and Sinclair, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture related knowledge management has become more and more popular (Ochieng 2009;Ochieng et al 2013;Zuofa and Ochieng 2015;Ovbagbedia and Ochieng, 2015). Economic conditions remain tough due to cut throat competition, globalisation, strategic operations against competition both local and global level (Ochieng et al 2016). Web Portal has become the most essential tool in the energy sector.…”
Section: Source: Carrillo 2004mentioning
confidence: 99%